Training medical students in human rights: a fifteen-year experience in Geneva - Chastonay, Philippe; Zesiger, Véronique; Ferreira, Jackeline; Kabengele Mpinga, Emmanuel (Revue canadienne de l'éducation médicale, 2012)
Background: Training health professionals in the field of human rights has long been advocated by the United Nations. Over the past decade some medical schools have introduced health and human rights courses, yet by far not all. This paper describes the objectives and the content of the Health and Human Rights program developed at the Faculty of Medicine, University of Geneva. Methods: The health and human rights program was developed through the identification of the course objectives, contents, and educational modalities using consensus techniques, and through a step by step implementation procedure integrating multiple evaluation processes. Results: Defined objectives included the familiarization with the concepts, instruments and mechanisms of human rights, the links between health and human rights, and the role of health professionals in promoting human rights. The content ultimately adopted focused on the typology of human rights, their mechanisms of protection, their instruments, as well as social inequalities and vulnerable groups of the population. The implementation proceeded through a step by step approach. Evaluation showed high satisfaction of students, good achievement of learning objectives, and some academic and community impact. Conclusions: High interest of students for a human rights course is encouraging. Furthermore, the community projects initiated and implemented by students may contribute to the social responsibility of the academic institution.